WEB-BASED SALES PERFORMANCE MANAGEMENT INFORMATION SYSTEM (CASE STUDY: PT. BINA ADIDAYA) - Kristanto, Dedy; Firdaus, Yaumil; Sari, Yunita Sartika (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
Completeness of information on PT. Bina Adidaya is still not efficient because it has to open sales data and bills that have been obtained by sales every month where the data cannot be seen if it is not in working hours. Therefore in making a website-based application that aims to provide information to management regarding sales-sales performance at PT. Build Superpower whenever and wherever needed. Sales performance can be measured by turnover, realization, and bills earned every month. Sales performance will be a reference material whether the sales are worth keeping by the company or not. The data that is needed by sales is only stored in the workspace, then the application helps provide information to sales if the sales are in the field.